SUSE LINUX Enterprise Server 9 Administrator's Handbook - Kuo, Peter; Beland, Jacques (Sams, 2005)
As a system administrator, you are justly concerned about the security of your infrastructure. SUSE Linux Enterprise Server (SLES 9) can lead the way to infrastructure security and SUSE Linux Enterprise Server Administrator's Handbook is the authoritative source for information on this secure server. Step-by-step procedures will walk you through installing and securing a SLES 9 system, and it will focus on the specific security features that make SLES 9 an important platform for all system administrators. Some of what you will cover is: SuSE server installation User access and security Installing and configuring networking services Securing your SuSE server Leverage Linux and open source with SLES 9 and SUSE Linux Enterprise Server Administrator's Handbook to build a secure computing network for your company.